2018
DOI: 10.1111/rda.13212
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of using previously used controlled internal drug release (CIDR) insert on the reproductive performance, hormone profiles and economic measures of sheep

Abstract: This study was conducted using 120 multiparous Awassi ewes during the breeding season to compare the effects of using previously used controlled internal drug release (CIDR) on the hormone profiles, reproductive performance and economic measures of ewes. Ewes were randomized to receive one of five previously used CIDR (previously used for 6, 12, 18, 24 or 30 days) or the new CIDR as a control for 6 days (CIDR6, CIDR12, CIDR18, CIDR24, CIDR30, and CIDR0 [control], respectively). Blood samples were collected on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 33 publications
(63 reference statements)
2
10
2
10
Order By: Relevance
“…However, with the dose of 200 IU of eCG it tended (P =0.078) to increase (Table 1). The high percentage of ewes that showed oestrus behaviour (95.31%) in response to the reused CIDR suggests that in the second use CIDRs still contain enough P 4 to cause LH blockage and allow the brain to respond to concentrations of circulating oestradiol, so that Insertion of CIDR Removal of CIDR Administration of eCG oestrous behaviour can be induced in the female (Swelum et al, 2018b). Previous studies have shown that when associated with eCG and a luteolytic agent, use for the third time in short protocols is viable for the synchronization and induction of oestrus and ovulation in ewes without affecting the percentages of oestrus presentation (Pinna et al, 2012;Bazzan et al, 2013;Vilariño et al, 2013;Da Silva et al, 2014) since the eCG favours follicular growth and the consequent production of oestradiol (Murphy, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, with the dose of 200 IU of eCG it tended (P =0.078) to increase (Table 1). The high percentage of ewes that showed oestrus behaviour (95.31%) in response to the reused CIDR suggests that in the second use CIDRs still contain enough P 4 to cause LH blockage and allow the brain to respond to concentrations of circulating oestradiol, so that Insertion of CIDR Removal of CIDR Administration of eCG oestrous behaviour can be induced in the female (Swelum et al, 2018b). Previous studies have shown that when associated with eCG and a luteolytic agent, use for the third time in short protocols is viable for the synchronization and induction of oestrus and ovulation in ewes without affecting the percentages of oestrus presentation (Pinna et al, 2012;Bazzan et al, 2013;Vilariño et al, 2013;Da Silva et al, 2014) since the eCG favours follicular growth and the consequent production of oestradiol (Murphy, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Elevation of serum P 4 concentration, which is influenced by the release of P 4 from the device, causes persistent follicle regression and inhibits the release of gonadotropins from the anterior pituitary gland, allowing blockage of oestrus behaviour and ovulation until withdrawal of the device (Swelum et al, 2018b). Subsequently, the inhibition disappears on the removal of the device, which causes the stimulation of the gonadotropin-releasing hormone pulse from the hypothalamus, which influences the preovulatory increase of LH and FSH that results in the re-start of ovarian activity, which culminates in ovulation (Laven, 2019;Martinez-Ros et al, 2019a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of adequate P4 concentrations during the preceding luteal phase for estrus expression is suggested, for example, by reports that estrus expression is reduced after synchronization with previously used controlled internal drug releasing (CIDRs) devices, which results in lower than normal P4 concentrations during the treatment [28,29]. However, if in the present study the differences in estrus expression between groups were related to differences in P4 concentrations during the preceding luteal phases, these differences must have been very subtle, because the general P4 profile and the average duration of the luteal phases were similar in all groups.…”
Section: Discussionmentioning
confidence: 99%